Potential phytomanagement of military polluted sites and biomass production using biofuel crop miscanthus x giganteus. (June 2019) - Pidlisnyuk, Valentina; Erickson, Larry; Stefanovska, Tatyana; Popelka, Jan; Hettiarachchi, Ganga; Davis, Lawrence; Trögl, Josef
Abstract: This study aims to summarize results on potential phytomanagement of two metal(loid)-polluted military soils using Miscanthus x giganteus . Such an option was tested during 2-year pot experiments with soils taken from former military sites in Sliač, Slovakia and Kamenetz-Podilsky, Ukraine. The following elements were considered: As, Cu, Fe, Mn, Pb, Sr, Ti, Zn and Zr. M. x giganteus showed good growth at both military soils with slightly higher maximum shoot lengths in the second year of vegetation. Based on Principal Component Analysis similarities of metal(loid) uptake by roots, stems and leaves were summarized. Major part of the elements remained in M. x giganteus roots and rather limited amounts moved to the aerial parts. Levels taken up decreased in the second vegetation year. Dynamics of foliar metal(loid) concentrations divided the elements in two groups: essential elements required for metabolism (Fe, Mn, Cu, and Zn) and non-essential elements without any known metabolic need (As, Sr, Ti, and Zr). Fe, Mn, Ti and Sr showed similar S-shaped uptake curve in terms of foliar concentrations (likely due to dilution in growing biomass), while Cu exhibited a clear peak mid-season. Behavior of Zn was in between. Foliar Zr and As concentrations were below detection limit. The results illustrated a good potential of M. x giganteus for safely growing on metal-polluted soils taken from both military localities. Graphical abstract: Image 1 Highlights: Potential phytomanagement with Miscathus x giganteus was proved while growing at the military soils. Principal Component Analysis revealed low variability of metal(loid)s behavior in upper parts of the plants. Dynamics of foliar metal(loid)s during two vegetation season was evaluated. Profound research is requested for understanding the mechanism of soil characteristic changing.